Copolymerization of epoxides with cyclic anhydrides catalyzed by dinuclear cobalt complexes - Hiranoi, Yo; Nakano, Koji (Beilstein Journal of Organic Chemistry, 2018)
The alternating copolymerization of epoxides with cyclic anhydrides (CAs) is a highly diverse synthetic method for polyesters as the polymers’ architectures and properties can be easily controlled depending on the combination of two monomers. Thus, a variety of catalyst designs has been reported to prepare the desired copolymers efficiently. We herein report dinuclear cobalt–salen complexes with a benzene ring as a linker and their activities in copolymerization reactions. The dinuclear cobalt complexes showed a higher catalytic activity for the copolymerization of propylene oxide with phthalic anhydride than the corresponding mononuclear cobalt–salen complex and achieved one of the highest turnover frequencies ever reported. A variety of epoxides and CAs were also found to be copolymerized successfully by the dinuclear cobalt complex with a high catalytic activity.
Keywords: cobalt; copolymerization; cyclic anhydrides; epoxides; polyesters

(untitled) - Hillmyer, M. A.; Tolman, W. B. (Acc. Chem. Res., 2014)

(untitled) - Coulembier, O.; Degée, P.; Hedrick, J. L.; Dubois, P. (Prog. Polym. Sci., 2006)

(untitled) - Gigli, M.; Fabbri, M.; Lotti, N.; Gamberini, R.; Rimini, B.; Munari, A. (Eur. Polym. J., 2016)

Degradable Aliphatic Polyesters - Albertsson, A.-C.; Varma, I. K. (Aliphatic Polyesters: Synthesis, Properties and Applications, 2002)

(untitled) - Albertsson, A.-C.; Varma, I. K. (Biomacromolecules, 2003)

Synthetic Biodegradable Polymers - Dutta, S.; Hung, W.-C.; Huang, B.-H.; Lin, C.-C. (Recent Developments in Metal-Catalyzed Ring-Opening Polymerization of Lactides and Glycolides: Preparation of Polylactides, Polyglycolide, and Poly(lactide-co-glycolide), 2012)

Synthetic Biodegradable Polymers - Lecomte, P.; Jérôme, C. (Recent Developments in Ring-Opening Polymerization of Lactones, 2012)

(untitled) - Lou, X.; Detrembleur, C.; Jérôme, R. (Macromol. Rapid Commun., 2003)

(untitled) - Thomas, C. M. (Chem. Soc. Rev., 2010)

Degradable Aliphatic Polyesters - Stridsberg, K. M.; Ryner, M.; Albertsson, A.-C. (Controlled Ring-Opening Polymerization: Polymers with designed Macromolecular Architecture, 2002)

(untitled) - Paul, S.; Zhu, Y.; Romain, C.; Brooks, R.; Saini, P. K.; Williams, C. K. (Chem. Commun., 2015)

(untitled) - Longo, J. M.; Sanford, M. J.; Coates, G. W. (Chem. Rev., 2016)

(untitled) - Fischer, R. F. (J. Polym. Sci., 1960)

(untitled) - Jeske, R. C.; DiCiccio, A. M.; Coates, G. W. (J. Am. Chem. Soc., 2007)

(untitled) - DiCiccio, A. M.; Longo, J. M.; Rodríguez-Calero, G. G.; Coates, G. W. (J. Am. Chem. Soc., 2016)

(untitled) - Van Zee, N. J.; Sanford, M. J.; Coates, G. W. (J. Am. Chem. Soc., 2016)

(untitled) - Robert, C.; de Montigny, F.; Thomas, C. M. (Nat. Commun., 2011)

(untitled) - DiCiccio, A. M.; Coates, G. W. (J. Am. Chem. Soc., 2011)

(untitled) - Hosseini Nejad, E.; van Melis, C. G. W.; Vermeer, T. J.; Koning, C. E.; Duchateau, R. (Macromolecules, 2012)

(untitled) - Jeon, J. Y.; Eo, S. C.; Varghese, J. K.; Lee, B. Y. (Beilstein J. Org. Chem., 2014)

(untitled) - Darensbourg, D. J.; Poland, R. R.; Escobedo, C. (Macromolecules, 2012)

(untitled) - Sanford, M. J.; Van Zee, N. J.; Coates, G. W. (Chem. Sci., 2018)

(untitled) - Winkler, M.; Romain, C.; Meier, M. A. R.; Williams, C. K. (Green Chem., 2015)

(untitled) - Van Zee, N. J.; Coates, G. W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Duan, Z.; Wang, X.; Gao, Q.; Zhang, L.; Liu, B.; Kim, I. (J. Polym. Sci., Part A: Polym. Chem., 2014)

(untitled) - Fournier, L.; Robert, C.; Pourchet, S.; Gonzalez, A.; Williams, L.; Prunet, J.; Thomas, C. M. (Polym. Chem., 2016)

(untitled) - Matsunaga, S.; Shibasaki, M. (Chem. Commun., 2014)

(untitled) - Park, J.; Hong, S. (Chem. Soc. Rev., 2012)

(untitled) - Delferro, M.; Marks, T. J. (Chem. Rev., 2011)

(untitled) - Matsunaga, S.; Shibasaki, M. (Bull. Chem. Soc. Jpn., 2008)

(untitled) - Liu, J.; Bao, Y.-Y.; Liu, Y.; Ren, W.-M.; Lu, X.-B. (Polym. Chem., 2013)

(untitled) - Garden, J. A.; Saini, P. K.; Williams, C. K. (J. Am. Chem. Soc., 2015)

(untitled) - Zhu, Y.; Romain, C.; Williams, C. K. (J. Am. Chem. Soc., 2015)

(untitled) - Yu, C.-Y.; Chuang, H.-J.; Ko, B.-T. (Catal. Sci. Technol., 2016)

(untitled) - Wu, L.-y.; Fan, D.-d.; Lü, X.-q.; Lu, R. (Chin. J. Polym. Sci., 2014)

(untitled) - Saini, P. K.; Romain, C.; Zhu, Y.; Williams, C. K. (Polym. Chem., 2014)

(untitled) - Thevenon, A.; Garden, J. A.; White, A. J. P.; Williams, C. K. (Inorg. Chem., 2015)

(untitled) - Zhu, L.; Liu, D.; Wu, L.; Feng, W.; Zhang, X.; Wu, J.; Fan, D.; Lü, X.; Lu, R.; Shi, Q. (Inorg. Chem. Commun., 2013)

(untitled) - Liu, D.-F.; Wu, L.-Y.; Feng, W.-X.; Zhang, X.-M.; Wu, J.; Zhu, L.-Q.; Fan, D.-D.; Lü, X.-Q.; Shi, Q. (J. Mol. Catal. A: Chem., 2014)

(untitled) - Hiranoi, Y.; Hatanaka, M.; Nakano, K. (J. Polym. Sci., Part A: Polym. Chem., 2017)

(untitled) - Cohen, C. T.; Chu, T.; Coates, G. W. (J. Am. Chem. Soc., 2005)

(untitled) - Liu, H.-X.; Dang, Y.-Q.; Yuan, Y.-F.; Xu, Z.-F.; Qiu, S.-X.; Tan, H.-B. (Org. Lett., 2016)